Avaliação nutricional de dietas utilizando palma orelha-de-elefante mexicana em substituição parcial ao feno de buffel na alimentação de caprinos e ovinos - Araújo, Cintia Mirely de (2017)
The objective of this work was to evaluate the replacement of Buffel hay by the Mexican elephant ear cactus, as forage, without causing nutritional and metabolic disturbances in sheep and goats, and to make a comparison, from the point of view nutritional value, of the efficiency of palm utilization by these species. The experiment was developed at the Small Ruminants Research Unit, belonging to the UFPB / CCA / Areia - PB. Ten animals were used, five goats with no defined racial pattern (SPRD) and five Santa Inês sheep, adults, castrated and cannulated in the rumen. The experimental design used was the double Latin square (5x5), each square being constituted by one species and the treatments were represented by the Buffel hay substitution levels by the Mexican elephant ear cactus in the proportions of 0; 20; 40; 60 and 80%. There was an interaction effect between diet and species for water consumption, where for the 0 and 20% levels of hay replacement by the palm, there was greater consumption by the goat species (2129.20 and 1243.86 mL) in relation to ovine (1518.60 and 822.02 mL). The dry matter intake (DMI) was not influenced by the treatments, for both goats and sheep. The consumption of ash (IA) and non-fibrous carbohydrates (NFC) by sheep increased linearly with the increase in the Buffel hay substitution level by Mexican elephant ear. NDF intake, both by goats and sheep, linearly reduced with hay replacement. The digestibility coefficients of the nutrients were not influenced by the experimental diets. There was a diet x species interaction effect for the total content (% BW), DM renewal time (h), DM disappearance rate (% / h) and for the digesta composition. The concentration of the AGV increased linearly with the increase of the cactus in the diets, for both species, since the pH was not influenced by the diets nor by the species, presenting values ranging from 6.24 to 6.39. The Mexican elephant ear cactus can replace the dietary hay, as bulky, up to the 80% level, without causing nutritional problems, for goats and sheep, however, they had divergence in response to experimental diets.